2011
DOI: 10.1016/s0254-6272(11)60014-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study on Treatment of the Earthquake-caused Post-traumatic Stress Disorder by Cognitive-behavior Therapy and Acupoint Stimulation

Abstract: The acupoint stimulation is effective for the PTSD patients, with better results than that of cognitive-behavior therapy used alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 1 publication
1
60
0
1
Order By: Relevance
“…So we included only 1 RCT with full data [25] from the 6 RCTs [25, 35–39]. Consequently, 4 RCTs [18, 25–27] and 2 UCTs [28, 29] met our inclusion criteria. Figure 1 sums up the search results based on a four-phase flow diagram in Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement format [40].…”
Section: Resultsmentioning
confidence: 99%
“…So we included only 1 RCT with full data [25] from the 6 RCTs [25, 35–39]. Consequently, 4 RCTs [18, 25–27] and 2 UCTs [28, 29] met our inclusion criteria. Figure 1 sums up the search results based on a four-phase flow diagram in Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement format [40].…”
Section: Resultsmentioning
confidence: 99%
“…In the only comparison study involving acupoint stimulation and CBT, 91 subjects with PTSD following an earthquake in China were randomly assigned to CBT treatment alone or CBT with acupoint stimulation. Participants in both groups improved, but the improvement for those whose treatment included acupoint stimulation was significantly stronger (p < .01) than the improvement for those who received CBT alone (Zhang, Feng, Xie, Xu, & Chen, 2011). While the study did not meet this review's inclusion criteria because it used an electronic acupoint stimulator instead of tapping, it is mentioned here because it suggests that acupoint stimulation might improve outcomes when used in combination with established modalities.…”
Section: Evidence By Conditionmentioning
confidence: 97%
“…Hollifield found that acupuncture was as effective as CBT when compared to a waitlist control, 23 and Zhang found that acupoint stimulation combined with CBT was more effective than CBT alone. 25 Because these are slightly different modalities, further research is warranted. GRADE B .…”
Section: Resultsmentioning
confidence: 99%